Transport Demand and Traffic Engineering Scheme in The Street Space Reallocation Plan For The Future Tram Track - Wahju Herijanto; Hera Widyastuti; Anak Agung Gde Kartika; Budi Rahardjo; Catur Arif Prastyanto; Istiar Istiar (Lembaga Penelitian dan Pengabdian kepada Masyarakat - Institut Teknologi Sepuluh Nopember, 2018)
Surabaya has the plan to reactivate tram in several arterial streets which will cause car lane reduction. This research aims to enhance the traffic performance of several arterial streets in Surabaya after the reduction of street width due to street space reallocation for the future tram track. The modal split analysis in a natural car and train or pulled scheme is compared to several vehicle restriction methods or push scheme which using data from car and motorcycle rider. From comprehensive computation, it is concluded that the insertion of tram track in the road space directly without any transport demand management will impact street performance to a more severe condition of traffic jam intersection. Therefore this research advising city government to apply restriction scheme to car and motorcycle by using high occupancy vehicle only scheme or prepaid area licensing scheme.